Comparison of Fluoride Uptake into Tooth Enamel Using Four Different Fluoride Varnishes - Moslemi, Masumeh; Asghari Moghaddam, Samira; iranparvar, parastoo; Kooshki, Fahimeh; Eskandarion, Solmaz (Journal of Dental School, 2024)
Objectives The efficacy of fluoride varnish in preventing dental caries has been well documented. The objective of this study was to compare the impact of four different fluoride varnish brands containing 5% sodium fluoride on the sound enamel of permanent teeth. Methods In this experimental study, 40 sound human premolar teeth were randomly assigned to four groups (Fluorilaq®, FluoroDose®, Preventa®, Kimia®; N=10). Each tooth was sectioned into buccal and lingual halves, corresponding to the control and the experimental subgroups, respectively. In the experimental halves, a semi-circular shaped area of the enamel was treated with the designated fluoride varnish. All specimens underwent Acid Etch Enamel Biopsy. Fluoride and Calcium concentrations were measured using a Potentiometer and Inductively Coupled Plasma optical emission spectrometer, respectively. The collected data were analyzed using paired t-test and one-way ANOVA at P<0.05. Results There was a significant difference between the enamel fluoride content of experimental and control halves in all groups (P<0.05). Preventa® Fluoride varnish caused the highest Fluoride uptake, followed by FluoroDose®, Fluorilaq®, and Kimia®. All pair comparisons were statistically significant (P<0.05), except for Preventa® vs. FluoroDose® (P=0.36). Conclusion Since all examined Fluoride varnishes increased the Fluoride content of the tooth enamel, they potentially qualify for caries prevention. Furthermore, Preventa® could be considered a good domestic alternative for other brands investigated in this research, in terms of enamel fluoride uptake.